Alternate wetting and drying (AWD) in Asia - CGIAR Research Program on Rice (2021)
AWD has been integrated in major national rice crop management guidelines in Vietnam, China and the Philippines and dissemination has started in all countries above. Several rice-producing countries mention AWD in their contributions to the Paris Agreement as effective mitigation instrument in the agriculture sector.